2010
DOI: 10.1007/s11912-010-0090-7
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cavity Squamous Cell Carcinoma and the Clinically N0 Neck: The Past, Present, and Future of Sentinel Lymph Node Biopsy

Abstract: Oral cavity squamous cell carcinoma (OCSCC) has a yearly incidence of 274,000 patients. Twenty percent to 30% of patients will harbor occult regional metastases, an important feature that correlates with worse outcomes. Supraomohyoid neck dissection (SND) is the gold standard treatment, but because of recent successes of sentinel lymph node (SLN) biopsy in the management of breast cancer and melanoma, many have begun evaluating its use in head and neck mucosal cancers. SLN biopsy offers patients decreased morb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 46 publications
0
36
1
3
Order By: Relevance
“…This cannot be studied by the SLNB [20]. c) Sentinel lymph node biopsy at two or more level requires general anaesthesia, operating time and cervical dissection, thus offering little benefit over selective neck dissection [7,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…This cannot be studied by the SLNB [20]. c) Sentinel lymph node biopsy at two or more level requires general anaesthesia, operating time and cervical dissection, thus offering little benefit over selective neck dissection [7,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the SLN for the presence of tumour cells proved itself beneficial for clinically occult regional disease exposure and more precise staging. 4 It is generally agreed that if on pathology and/or immunohistochemistry the SLN turns out to be negative, the patient may be spared from the potential morbidity of the regional lymphoadenectomy and the status of SLN presents an accurate indication of the condition of the rest of the regional nodes. 5 Diseasepositive SLN are correlated with higher locoregional recurrence rates and a poor survival prognosis even in the presence of a therapeutic neck dissection and adjuvant therapy.…”
Section: Introductionmentioning
confidence: 99%
“…33 The techniques and methodology for SLN identification in head and neck cancers have been widely debated and are still under investigation [ Tables 1 and 2]. 5,14,15,22,24,[27][28][29][30][31][34][35][36][37][38][39][40][41][42][43][44][45][46] Shoaib et al suggested a protocol involving preoperative lymphoscintigraphy, intraoperative blue dye and gamma probe localisation [ Figure 2]. 30 This technique is based on observing the route of lymphatic flow via imaging after the injection of a radioactive contrast agent near the primary tumour.…”
mentioning
confidence: 99%
“…30 This technique is based on observing the route of lymphatic flow via imaging after the injection of a radioactive contrast agent near the primary tumour. 42 The flow and direction of the lymph, comparable to the possibly metastatic flow from the tumour, can be visualised preoperatively by means of lymphoscintigraphy or single-photon emission computed tomography (SPECT). Lymphoscintigraphy reveals SLNs associated with the primary tumour, unexpected lymphatic drainage patterns and lymphatic vessels associated with different lymphatic drainage basins.…”
mentioning
confidence: 99%